The RS Oph Outburst of 2021 Monitored in X-Rays with NICER - Orio, Marina (2023)
The 2021 outburst of the symbiotic recurrent nova RS Oph was monitored with the Neutron Star Interior Composition Explorer Mission (NICER) in the 0.2-12 keV range from day one after the optical maximum, until day 88, producing an unprecedented, detailed view of the outburst development. The X-ray flux preceding the supersoft X-ray phase peaked almost 5 days after optical maximum and originated only in shocked ejecta for 21-25 days. The emission was thermal; in the first 5 days, only a non-collisional-ionization equilibrium model fits the spectrum, and a transition to equilibrium occurred between days 6 and 12. The ratio of peak X-ray flux measured in the NICER range to that measured with Fermi in the 60 MeV-500 GeV range was about 0.1, and the ratio to the peak flux measured with H.E.S.S. in the 250 GeV-2.5 TeV range was about 100. The central supersoft X-ray source (SSS), namely the shell hydrogen burning white dwarf (WD), became visible in the fourth week, initially with short flares. A huge increase in flux occurred on day 41, but the SSS flux remained variable. A quasi-periodic oscillation every ≃35 s was always observed during the SSS phase, with variations in amplitude and a period drift that appeared to decrease in the end. The SSS has characteristics of a WD of mass >1 M ⊙. Thermonuclear burning switched off shortly after day 75, earlier than in the 2006 outburst. We discuss implications for the nova physics.